Literary and Artistic Magazine Publishing in Turkey: The First Period Sample of Hareket Magazine - (:unkn) unknown (MARMARA UNIV, FAC COMMUNICATION, 2018)
The magazines are types of publications that present to its readers a rich content and have a comprehensive structure on various topic such as idea, art, culture and literature. The Hareket Magazine, which started publishing life in Turkey's single-party period (1923-1950), is a critical idea and art magazine. In this study, the issues of Hareket Magazine published in 1939 were analyzed in the context of conservatism, nationalism and religion. Two separate methods were used in the study; qualitative data analysis and content analysis. The magazine publications reached through qualitative data analysis were analyzed by means of content analysis method within the frame of nationalism and religion. The magazine aims to give a specific idea for readers in the sense of nationalism, Anatolia as a homeland of Muslim Turks, morals and movement philosophy. In this context, the study provides a perspective and description generally about Hareket Magazine which was on literature and art and was published in the single party regime. As a result of the research, the opposition stance of the Hareket journal in the conditions of publication of the Single Party period and its contribution to the intellectual-artistic magazine publishing was evaluated in terms of nationalism and religion issues.
Keywords: Publishing; Magazines; Literary and Artistic Magazine; Hareket Magazine